Latent heat thermal energy storage in a shell-tube: A wavy partial layer of metal foam over tubes. (March 2023) - Ghalambaz, Mehdi; Aljaghtham, Mutabe; Chamkha, Ali J.; Fteiti, Mehdi; Abdullah, Abdelkader
Abstract: The melting thermal energy storage and heat transfer of paraffin wax in a storage unit was modeled in the presence of a wavy copper foam. The phase-change energy and natural convection effects were modeled using the enthalpy porosity approach. The control equations were solved using the finite element method over a structured mesh. The energy storage was simulated for the wavenumber and amplitude of the foam layer. It was found that the higher wavenumber, the shorter the charging time and better energy storage power. A lower wave magnitude was also better than a longer wave magnitude. The shortest melting time was obtained for a flat foam layer, which was 20 % better than a low wave long amplitude foam layer. The current work intends to reduce the weight of applied metal foams in thermal energy storage applications by enhancing the geometry design. Here, a wavy form layer of metal foam was used to guide the natural convection flows and also boost the heat transfer mechanism. The phase change heat transfer has not been investigated in a wavy form metal foam layer. Highlights: The thermal energy storage in the presence of a wavy copper foam was addressed. The energy storage was simulated for the wavenumber and amplitude of the foam layer. Integration of the enthalpy porosity and the finite element method was used. A flat foam layer could reduce the melting time by 20 %.